2021
DOI: 10.1093/cid/ciab145
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of Fluoroquinolones in Patients with Staphylococcal Periprosthetic Joint Infections

Abstract: Background Fluoroquinolones (FQs) are known to be accompanied by significant risks. However, the incidence of adverse events (ADE) resulting in unplanned drug discontinuation when used for periprosthetic joint infections (PJI) is currently unknown. Methods This study included 156 patients over the age of 18 treated for staphylococcal PJI with debridement, antibiotics, and implant retention (DAIR), between January 1, 2007 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Fluoroquinolones (FQs) belong to a class of broad-spectrum antibiotics used to kill various microorganisms [ 1 , 2 ]. During the last two decades, newer fluoroquinolones have been introduced into the market [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fluoroquinolones (FQs) belong to a class of broad-spectrum antibiotics used to kill various microorganisms [ 1 , 2 ]. During the last two decades, newer fluoroquinolones have been introduced into the market [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most international guidelines have adopted rifampicin combination therapy as the cornerstone antibiotic treatment for staphylococcal PJI treated with DAIR, based on experimental animal models, 1 randomized trial, and several cohort studies. However, rifampicin combination therapy is associated with significant side effects and drug-drug interactions, making its use less patient-friendly [ 4 , 5 ]. Moreover, the literature regarding the effect of rifampicin combination therapy against staphylococcal hip and knee PJI after DAIR has not yet been explored systematically.…”
mentioning
confidence: 99%
“…It is possible that ID providers are not comfortable in selecting fluoroquinolone as a drug of choice for S. aureus BJI in the United States. 23 Our 6-month recurrence rates were 21.3% in patients treated with OPAT and 34.2% in patients treated with oral antibiotics. These recurrence rates were higher than those reported in the OVIVA trial, which reported 1-year recurrence rates of 14.6% in OPAT group and 13.2% in the oral antibiotic group.…”
Section: Discussionmentioning
confidence: 57%